Enhancing the crop yield through capacity building programs: application of double difference method for evaluation of drip capacity building program in Tamil Nadu State, India - Kuppannan, Palanisami; Ranganathan, C.R.; Sureshkumar, D.; Malik, Ravinder Paul Singh (Scientific Research Publishing, Inc., 2014)
A capacity building program on drip irrigation (TNDRIP) was undertaken in certain regions of the Indian State of Tamil Nadu during 2009-2010. An assessment of the impact of the program in terms of effective use of drip irrigation and in-creased crop yields was made in 2011 by ap-plying double difference method (a combination of both with and without and before and after approaches). The results had indicated that the drip capacity building program resulted in a yield increase of 2.5 t/ha for Banana 1, 1.9 t/ha for Banana 2, 3.3 t/ha for sugarcane and 0.3 t/ha for turmeric. The conventional method using the before and after situations had shown a yield increase of 4.3 t/ha for Banana 1, 12.1 t/ha for Banana 2, 40.6 t/ha for sugarcane and 2.6 t/ha for turmeric. The conventional approach is highly upward biased in estimating the impact of the drip capacity building program and thus the double difference method will be an appropriate method to evaluate the impact of the programs that involve both with and without as well as before and after situations.